Cultural determinants of capital structure in Indonesian banking: A macroeconomic context - Saleh, Rinaldy; Isnurhadi; Malinda, Shelfi; Widiyanti, Marlina (International research journal of management, IT and social sciences, 2024)
Capital structure decisions play a crucial role in shaping the financial landscape of companies, especially in developing countries. This study examines the cultural determinants of capital structure in Indonesian banking within the macroeconomic context from 2013 to 2022. The capital structure represents the mix of various company funding methods, impacting its value and influencing stakeholders. The debate on how the interplay of debt and assets affects a company’s value continues, with the determining factors of capital structure still being explored in financial studies. Using STATA V.17, this research analyzes 30 banking companies listed on the Indonesia Stock Exchange, with leverage as the dependent variable. Financial ratios, including liquidity ratio, profit volatility, growth opportunities, bank size, and external macroeconomic variables such as inflation and Gross Domestic Product (GDP), are examined as potential influencers on the capital structure. The results reveal high leverage in Indonesian banks, with variations in financial approaches. Return on assets, growth opportunities, and inflation exhibit a positive and significant relationship with leverage, while profit volatility, tangibility, bank size, and GDP show a negative and significant relationship. The research suggests limitations in scope, recommending including all Indonesian banking companies and additional external macroeconomic variables like exchange and interest rates.